Flexible layouts for the mixed-model assembly of heterogeneous vehicles - Hottenrott, Andreas (Springer Nature, 2020)
The increasing vehicle heterogeneity is pushing the widespread mixed-model assembly line to its limit. The paced, serial design is incapable of coping with the diversity in workloads and task requirements. As an alternative, the automotive industry has started to introduce ﬂexible layouts for segments of the assembly. In ﬂexible layouts, the stations are no longer arranged serially and no longer linked by a paced transportation system but by automated guided vehicles. This paper investigates the initial conﬁguration of such systems. The ﬂexible layout design problem (FLDP) is the problem of designing a ﬂexible layout for a segment of the assembly of heterogeneous vehicles. It comprises an integrated station formation and station location problem. Moreover, the FLDP anticipates the operational ﬂow allocation of the automated guided vehicles. We formalize the FLDP in a mixed-integer linear program and develop a decomposition-based solution approach that can optimally solve small- to mid-sized instances. In addition, we transform this solution approach to a matheuristic that generates high-quality solutions in acceptable time for large-sized instances. We compare the efﬁciency of ﬂexible layouts to mixed-model assembly lines and quantify the beneﬁts of ﬂexible layouts which increase with vehicle heterogeneity.